Key issues in professionalizing mentoring practices - Stoeger, Heidrun; Balestrini, Daniel Patrick; Ziegler, Albert (Annals of the New York Academy of Sciences, 2020)
Mentoring has experienced a tremendous upswing over the past decades, which has only recently slowed down somewhat. One possible factor explaining mentoring's popularity are numerous case studies suggesting that it is one of the most effective ways of helping individuals to develop. Meta-analyses indicating effect sizes for mentoring that are below what would theoretically be possible appear to contradict the success stories, however. This circumstance raises questions about the professionalization of mentoring practices. We focus on seven key issues for future efforts at professionalizing mentoring. Key issues 1 and 2 address observation of the state of the art within formal mentoring when programs are planned and implemented: the consideration of recent research and of best practices. While both areas can overlap, they provide complementary sources of pertinent information for the professionalization of mentoring. Key issues 3-6 address the need to align mentoring activities to the specific context and goals of individual mentoring programs by observing idiographic program characteristics, mentoring dynamics, the orchestration of mentoring goals, and the provision of mentoring resources. Finally, key issue 7 highlights ongoing evaluation as the basis of the effective, continuous improvement of mentoring programs.
CRIS-Team WoS Importer:2020-12-18